Nephrocalcinosis as a complication of subcutaneous fat necrosis of the newborn - Canpolat, Nur; Özdil, Mine; Kuruğoğlu, Sebuh; Çalışkan, Salim; Sever, Lale (The Turkish Journal of Pediatrics, 2012)
Subcutaneous fat necrosis of the newborn is an uncommon disorder affecting the adipose tissue of term infants. It is usually known as a transient, benign and self-limited disease, characterized by painful skin lesions beginning within the first week of life. The prognosis of the disease is generally good, but it may be complicated by potentially life-threatening metabolic alterations, including hypercalcemia, thrombocytopenia, hypoglycemia, and hypertriglyceridemia. Hypercalcemia is the most serious complication of subcutaneous fat necrosis because of its effects on the renal and cardiovascular systems. We thereby present a case of subcutaneous fat necrosis with all these metabolic alterations, which was also complicated by nephrocalcinosis as a non-transient and serious complication.